Cubic Membranes Formation in Synchronized Human Hepatocellular Carcinoma Cells Reveals a Possible Role as a Structural Antioxidant Defense System in Cell Cycle Progression - Kong, Deqin; Liu, Rui; Liu, Jiangzheng; Zhou, Qingbiao; Zhang, Jiaxin; Li, Wenli; Bai, Hua; Hai, Chunxu (Frontiers in Cell and Developmental Biology, 2020)
Cubic membranes (CMs) represent unique biological membrane structures with highly curved three-dimensional periodic minimal surfaces, which have been observed in a wide range of cell types and organelles under various stress conditions (e. g., starvation, virus-infection, and oxidation). However, there are few reports on the biological roles of CMs, especially their roles in cell cycle. Hence, we established a stable cell population of human hepatocellular carcinoma cells (HepG2) of 100% S phase by thymidine treatment, and determined certain parameters in G2 phase released from S phase. Then we found a close relationship between CMs formation and cell cycle, and an increase in reactive oxygen species (ROS) and mitochondrial function. After the synchronization of HepG2 cells were induced, CMs were observed through transmission electron microscope in G2 phase but not in G1, S and M phase. Moreover, the increased ATP production, mitochondrial and intracellular ROS levels were also present in G2 phase, which demonstrated a positive correlation with CMs formation by Pearson correlation analysis. This study suggests that CMs may act as an antioxidant structure in response to mitochondria-derived ROS during G2 phase and thus participate in cell cycle progression.